Comparative study: repair of congenital inguinal hernia with and without opening the inguinal canal - Fakhry, Tamer; Elhaw, Hassan Ibrahim; Fawzy, Ahmed Nabil (International Surgery Journal, 2021)
Background: Inguinal herniotomy is the most common surgery performed by paediatric surgeons. Methods: 100 Male and female cases with congenital inguinal hernia aging from one month till the age of two years. randomly allocated into two groups for undergoing two types of hernia repair techniques, with and without opening the external oblique muscle fascia. Surgical complications such as fever, scrotal oedema and hematoma, and wound infections classified as early complication. The rates of mentioned early complications and operative time were compared in the two interventional groups. In this study, 100 cases were selected and allocated to the two interventional groups. Results: The prevalence of early complications in two studied groups were not different significantly in two interventional groups. Operation time was significantly shorter in inguinal repair techniques without opening the external oblique muscle fascia than the other studied technique Conclusions: The findings of our study indicated that though early complications of the two repair methods were similar, but the time of procedure was shorter in herniotomy without opening the external oblique muscle both methods are safe and feasible, choosing one of them depend on surgeon prefer.